Adsorption Of Enrofloxacin From Aqueous Solution Using Teak Sawdust Hydrochar : Effects Of Particles Size, Adsorben Dosage, Contact Time And Watermatriks - Uswatun Khabiba Amalia; Muchammad Tamyis (CV Edujavare Publishing, 2026)
Water pollution due to antibiotic residues is worsening and endangering the environment because it can cause antibiotic exhaustion and damage aquatic ecosystems. One antibiotic frequently found in the environment is enrofloxacin, which originates from livestock activities and household waste. This study aimed to determine how well hydrochar from teak sawdust can absorb enrofloxacin and to determine the optimal conditions for this absorption process. Hydrochar was made through a hydrothermal carbonization process using teak sawdust at a temperature of 200 degrees Celsius for 10 hours. Testing was carried out by assessing the impact of particle size (120, 140, and 160 mesh), solution acidity level, amount of adsorbent used, initial enrofloxacin concentration, type of water medium, and contact duration. Enrofloxacin concentration was measured using a UV-Vis spectrophotometer with a wavelength of 340 nm, while adsorbent properties were analyzed using Fourier Transform Infrared Spectroscopy (FTIR). The study showed that hydrochar with a 120 mesh size had the best and most consistent absorption capacity compared to other sizes. FTIR analysis showed the presence of hydroxyl groups (O–H), aliphatic C–H compounds, aromatic C=C bonds, and C–O groups involved in the adsorption process. The adsorption efficiency increased with increasing contact time and reached its highest level of 37% at 180 minutes. The study showed that hydrochar from teak wood powder can be used as an environmentally friendly adsorbent alternative to remove enrofloxacin from water.